Landscape and authority in the early modern world - Whiteman, Stephen H. (Penn studies in landscape architecture., 2023)
"In Landscape and Authority in the Early Modern World, contributors explore the role of landscape in the articulation and expression of imperial identity and the mediation of relationships between the court and its many audiences in the early modern world. Nine focused studies from East andSouth Asia, the Islamic world, and Europe illuminate how early modern courts and societies shaped, and were shaped by, the landscape, including both physical sites, such as gardens, palaces, cities and hunting parks, and conceptual ones, such as those of frontiers, idealized polities, and the cosmos"--